Preparing athletes for competition in the heat: Developing an effective acclimization strategy - Maughan, R. J.; Shirreffs, S. M. (1997)
1. Heat and dehydration can be an athlete's fiercest competitors. 2. Heat exposure and dehydration impair performance, and their negative effects are additive. 3. Acclimatization will reduce the negative impact of heat on athletic performance. 4. Acclimatization is most effectively achieved by exercise in the heat; heat without exercise and exercise without heat are less effective. 5. Acclimatization can be carried out by exercising in a hot room or by training in a hot climate. 6. The major physiological adjustments to heat acclimatization take about 7-14 days. 7. Training volume and intensity should be reduced on first exposure to the heat and then gradually increased. Some high-intensity training should be maintained throughout the acclimatization period. 8. Reducing the intensity and duration of the warm-up may be necessary to keep core temperature from rising too high before training and competing in the heat. 9. Monitoring responses of individual athletes is essential -- individuals respond differently to physical activity in the heat. 10. Records of body mass, urine output and color, and subjective symptoms should be kept by athletes and reviewed periodically by coaches and trainers. 11. Acclimatization increases the athlete's need for fluid to match the increase in sweat rate. 12. Dehydration impairs performance and negates the beneficial effects of acclimatization. 13. An adequate intake of an appropriate fluid before, during, and after training and competition is essential to ensure an optimal response to exercise in the heat.